Humanitarian sukuk: practical instrument in eliminating refugee crisis - Mohd. Zain, Nor Razinah; Mahadi, Nur Farhah; Engku Ali, Engku Rabiah Adawiah (International Research Centre of Islamic Economics and Finance (IRCIEF), 2018)
Reaching towards 2018, the modern world sees the worst of refugees’ crisis after the War World II. With massive movement of refugees caused by war and genocide, these refugees are facing starvation and deprivation of human rights beyond imagination. This research explores the understanding on sustainable development goals in facing the refugee crisis and the potentials of Sukuk as alternative financing in overcoming it. Based on the collected secondary data and qualitative approach, the researchers analysed the potentials of Sukuk in financing refugees to overcome their state of incapability. The researchers found that the Sukuk has high potentials to be used as alternative financing in overcoming refugee crisis. It is also a practical instrument in eliminating the refugee crisis. In this study, the researchers proposed certain structures of Sukuk that can be adopted in financing humanitarian aids to overcome the refugee crisis.